Duck karyopherin α4 (duKPNA4) is involved in type I interferon expression and the antiviral response against Japanese encephalitis virus. (March 2020) - Li, Chenxi; Di, Di; Wang, Xin; Xia, Qiqi; Wahaab, Abdul; Anwar, Muhammad Naveed; Li, Zongjie; Liu, Ke; Shao, Donghua; Qiu, Yafeng; Wei, Jianchao; Li, Beibei; et al.
Abstract: Karyopherin α4 (KPNA4) is an adaptor molecule that mediates type I interferon (IFN) production by facilitating the nuclear translocation of IFN transcription factors. Here, we cloned the duck KPNA4 (duKPNA4) gene and analyzed its involvement in type I IFN expression as well as antiviral response against Japanese encephalitis virus (JEV). The full-length duKPNA4 gene encoded a 520-amino acid protein that shared 97.3–98.7% sequence similarity with its orthologues in chickens, humans and mice. The duKPNA4 was extensively expressed in various duck tissues at the mRNA level. Analysis of the subcellular localization of duKPNA4 by immunofluorescence assays indicated that the duKPNA4 was primarily distributed in both the cytoplasm and nucleus in primary duck embryonic fibroblasts (DEFs). However, it translocated from the cytoplasm to the nucleus in response to poly(I:C) stimulation or JEV infection. The duKPNA4 interacted with duck IFN regulatory factor 7 and facilitated its nuclear translocation, thereby up-regulating the expression of IFN-α and IFN-β in DEFs in the presence of poly(I:C) stimulation. Exogenous expression of duKPNA4 significantly elevated the expression of IFN-α and IFN-β induced by JEV infection and inhibited JEV replication in DEFs. These data demonstrate the importance of duKPNA4 in type I IFN signaling as well as the antiviral response against JEV replication. Highlights: duKPNA4 elevates type I IFN expression. duKPNA4 promotes the nuclear translocation of duIRF7. duKPNA4 inhibits JEV replication.